An Effective Osteogenesis Porous CaP/Collagen Interface Compatible with Various Substrates Fabricated by Controlled Mineralization in a Delicately Adjustable Organic Matrix. Issue 71 (18th November 2019) - Ma, Zequn; Li, Weiyang; Zhang, Yihe; Shi, Rui; Zhang, Yi; Zhang, Jingshuang; Li, Xiangming; Lu, Limei; An, Qi
Abstract: Increasing bone formation on the surfaces of implants such as screws, plates, or shims holds great significance for clinical medicine. However, osteogenesis implant coatings that mimic natural bone in terms of both their components and structural features are still lacking. Here we report the biomimetic interface of calcium phosphate (CaP) in a collagen matrix fabricated by controlled mineralization that presents biomimetic porous features. The porous CaP/collagen interface, with a thickness of about 1 μm, significantly enhances osteogenesis, as verified at both the gene and protein levels as well as by in vivo experiments. Taking advantage of the generality of the method, the biomimetic interface was prepared on a variety of substrates, including conductive substrates, 3D metal meshes, plastic or elastic substrates, and even on filter papers. The adjustability and generality of the method have enabled new characterization tests to be developed during experiments on cells and thus should greatly facilitate clinical medicine and tissue engineering. Abstract : Interface biomimics : We propose a biomimetic surface modification strategy to prepare porous calcium phosphate structures in a collagen/poly(ethylene glycol) (COL/PEG) matrix to boost osteoinductive effects (see figure). Moreover, the interfacial composite structure can be conveniently prepared on a wide variety of substrates, which enabled the detection of alkaline phosphatase in the osteogenic process, without the need to terminate the cells, by using conductive substrate surfaces.